Family Mediation in Ireland. - Conneely, Sinéad (Taylor and Francis, 2017)
"This title was first published in 2002: After outlining the origins and development of family mediation on a world-wide basis, this book assesses family mediation services in the Republic of Ireland and Northern Ireland, within the context of the empirical and theoretical debates surrounding the practice. It is the first comprehensive study of the area in Ireland, appearing at an opportune time, due to the expansion of the service in the Republic and its virtual collapse in Northern Ireland. It argues that the service provided in the Republic of Ireland is appreciated by clients and is successful, although the issue of domestic violence remains. In contrast, it suggests that the absence of service provision in Northern Ireland is problematic, since it undermines consumer choice."--Provided by publisher.